Ionic Liquids as Extractants for Nanoplastics. Issue 20 (8th September 2020) - Elfgen, Roman; Gehrke, Sascha; Hollóczki, Oldamur
Abstract: Plastic waste in the ocean and on land in the form of nanoplastics is endangering food and drinking water supplies, raising the need for new strategies for the removal of plastic nanoparticles from complex media. In the present contribution we suggest considering ionic liquids as extractants, since they show several advantageous properties that may facilitate the design of efficient separation processes. Through varying the anion and the side chain at the cation, the interactions between the extractant and the polymer can be strengthened and tuned, and thereby the disintegration of the particle into separate polymer chains can be controlled. Oxidized moieties can also be efficiently solvated, given the amphiphilic nature of the considered ionic liquids, allowing also realistic particles to be extracted into these solvents. The phase transfer was found to be thermodynamically and kinetically possible, which is supported by the complicated structure of the ionic liquid‐water interface through the rearrangement of the interfacial ions, and the formation of a micelle around the plastic already at the edge of the aqueous phase. Abstract : Hydrophobic ionic liquids are suggested as extracting solvents for the removal of nanoplastics from aqueous systems, to reduce the concentration of these potentially hazardous materials. Based on molecular modeling, comparison with molecular solvents reveal clear advantages for ionic liquids in terms of solvation and disintegration of the plastic particle, and the phase transfer mechanism. The results suggest ways of tuning and improving an extraction process.